Identifikasi dan Karakterisasi Strain Lactobacillus dan Khamir Asal Ragi Tape Singkong ( Manihot Utilissima) sebagai Agen Probiotik Baru - Nayla Azzahrah; Ardi Mustakim (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Cassava tape is a traditional fermented food that is popular in Indonesia and is known to contain potential microorganisms such as Lactobacillus spp. and yeast. These microorganisms play a significant role in the fermentation process of cassava tape, which in turn contributes to the product's taste and texture. Moreover, these microbes have the potential to act as probiotics, supporting gut health. This study aims to identify and characterize Lactobacillus strains and yeast isolated from cassava tape yeast, as well as evaluate their probiotic potential. Isolation was carried out using selective media specifically formulated for isolating Lactobacillus and yeast. After isolation, identification was performed through morphological, biochemical, and molecular approaches. Molecular identification was carried out using the 16S rRNA gene for Lactobacillus, while the Internal Transcribed Spacer (ITS) gene was used for yeast. After identification, probiotic characterization was carried out through several tests, including resistance to low pH, bile salts, antimicrobial activity against pathogens, and microbial adhesion to intestinal surfaces. The results of the study showed that several isolates of Lactobacillus plantarum and yeast such as Saccharomyces cerevisiae exhibited good resistance to simulated gastrointestinal conditions, including resistance to low pH and bile salts. Furthermore, these microbes showed antagonistic activity against the pathogens Escherichia coli and Staphylococcus aureus, indicating their ability to inhibit the growth of pathogenic bacteria in the digestive tract. These findings suggest that microbial strains isolated from cassava tape yeast have the potential to be developed as new local probiotic candidates. Therefore, cassava tape not only serves as a delicious traditional fermented food but also can be utilized to support gut health, providing a safe and beneficial probiotic alternative for the community.